2022
DOI: 10.1093/femspd/ftac038
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvants to increase immunogenicity of SARS-CoV-2 RBD and support maternal–fetal transference of antibodies in mice

Abstract: Adjuvants are important components of vaccines, increasing immunogenicity and modulating the immune response. SARS-CoV-2 vaccines are still being developed in order to improve worldwide access to immunization. Specific populations should be addressed in these investigations, such as pregnant women – to protect both mothers and neonates. In this study, female adult mice were immunized with Receptor-binding domain (RBD) from SARS-CoV-2 adjuvanted by a mixture of DDA and Saponin and put to mating to verify the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 70 publications
3
18
0
Order By: Relevance
“…In view of this, we studied an antigenic preparation using different adjuvants, aiming to induce a functional, durable and robust humoral and cellular response in mice. The first part of this study, published previously [19], showed that the same adjuvant contributed to the functionality of the humoral response and led to passive transfer of antibodies to the offspring. We used recombinant Receptor binding domain (RBD), due to its high immunogenicity and potential to induce neutralizing antibodies [4], associated with the following adjuvants mixtures: dimethyldioctadecylammonium bromide and saponin (DDA/Sap) or Outer membrane vesicles and aluminum hydroxide (OMV/AH).…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…In view of this, we studied an antigenic preparation using different adjuvants, aiming to induce a functional, durable and robust humoral and cellular response in mice. The first part of this study, published previously [19], showed that the same adjuvant contributed to the functionality of the humoral response and led to passive transfer of antibodies to the offspring. We used recombinant Receptor binding domain (RBD), due to its high immunogenicity and potential to induce neutralizing antibodies [4], associated with the following adjuvants mixtures: dimethyldioctadecylammonium bromide and saponin (DDA/Sap) or Outer membrane vesicles and aluminum hydroxide (OMV/AH).…”
Section: Introductionmentioning
confidence: 81%
“…We used recombinant Receptor binding domain (RBD), due to its high immunogenicity and potential to induce neutralizing antibodies [4], associated with the following adjuvants mixtures: dimethyldioctadecylammonium bromide and saponin (DDA/Sap) or Outer membrane vesicles and aluminum hydroxide (OMV/AH). We already published the results concerning IgG response and its functionality by avidity and neutralization against Wuhan strain [19]. In this manuscript, we continued the study, assessing IgM levels and avidity; IgG and IgM response one year after the immunization; neutralization against Omicron strain and memory-cellular response by ELISpot.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations